Improving Reading Skills of Grade II Students at SD Negeri 26 Tanjung Raja Through the Phonics Method - Indah Puspita Sari; Synthia; Triya Fitriyani; Tedy Kurniawan (Lombok Institute, 2026)
This classroom action research aimed to improve the reading skills of Grade II students at SD Negeri 26 Tanjung Raja through a structured phonics method. The study used Kurt Lewin's action research model, which consists of planning, action, observation, and reflection. The research was conducted in two cycles involving 26 students as the research subjects. Data were collected through a diagnostic reading test, reading performance tests, observation sheets, and teacher reflection notes. The data were analyzed descriptively by comparing students' mean scores, mastery percentages, reading speed, and blending accuracy across the pretest, Cycle I, and Cycle II. The findings showed a consistent improvement in students' reading skills. The mean reading score increased from 55.38 in the pretest to 69.80 in Cycle I and 81.30 in Cycle II. Classical learning mastery increased from 26.9% at the initial stage to 65.4% in Cycle I and 92.3% in Cycle II. Reading speed also improved from 5.1 words per minute to 15.7 words per minute, while blending accuracy reached 89.6% at the end of Cycle II. These results indicate that the structured use of phonics, supported by sound cards, phonemic songs, and repeated blending practice, helped students recognize phoneme-grapheme relationships and read words more accurately. The findings are limited to the classroom context studied and should be interpreted as evidence of improvement through classroom action rather than as a controlled test of effectiveness.